EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENTS (TGT) DENGAN METODE DISCOVERY PADA MATERI BANGUN RUANG SISI DATAR DITINJAU DARI KEMAMPUAN SPASIAL SISWA KELAS VIII SMP NEGERI DI KABUPATEN ROKAN HULU TAHUN PELAJARAN 2013/2014 - Nurrahmawati Nurrahmawati; Budiyono Budiyono; Imam Sujadi (Jurnal Pembelajaran Matematika, 2014)
Abstract: The purpose of this study are to determine the effect of the learning models on the learning achievement in Mathematics viewed from the spatial intelligence of the students. The learning models compared were the cooperative learning model of the TGT type with discovery method, the cooperative learning model of the TGT type, and the direct instruction model. The type of this study was a quasi-experimental study with a 3x3 factorial design. The study population was all grade VIII students of Junior High School in Rokan Hulu Regency. Instruments used for data collection were mathematics achievement test and spatial intelligence test. Based on the hypothesis, the results could be concluded as follows. (1) Students who were treated with the Teams Games Tournaments (TGT) cooperative learning model with discovery method had better learning achievement than students treated by TGT models and direct instruction model. In addition, students who were treated with the TGT model gave the same achievement with students treated by direct instruction model. (2) Students with high spatial intelligence had better learning achievement than the students with middle and low spatial intelligence. In addition, students who had middle spatial intelligence have better learning achievement than students who had low spatial intelligence. (3) In the spatial intelligence category of high, middle and low, the students’ learning achievement treated Teams Games Tournaments (TGT) cooperative learning model with discovery method was better than the students treated by TGT and direct instruction models. In addition, students treated by TGT model gave the same learning achievement with students treated by direct instruction model. (4) In the Teams Games Tournaments (TGT) cooperative learning model with discovery method, TGT model and direct instruction model, the students who had high spatial intelligence had better learning achievement than middle and low spatial intelligence. In addition, the students who had middle spatial intelligence had better learning achievement than students who had low spatial intelligence.Keywords: Teams Games Tournaments (TGT), Disccovery Method, Spatial Intelligence.